The Effect of Google Classroom Use on Learning Media Design Ability and Teacher Professionalism at SMPN 3 Mandau - Ernita, Ernita; Sa'ud, Udin Syaefudin; Luthfi, Amir (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of using Google Classroom on the ability to design learning media and teacher professionalism at SMPN 3 Mandau. The method used is a quantitative approach with a quasi-experimental research design. The population in this study were 20 teachers at SMPN 3 Mandau, sampling was carried out using the total sampling technique. Data were collected through observation sheets distributed to 20 teachers, consisting of 10 observation aspects for the variable of the ability to design learning media, and 15 observation aspects for the variable of teacher professionalism. The results showed that the use of Google Classroom had a significant positive effect on the ability to design learning media with a coefficient value of 0.000 0.05. In addition, the use of Google Classroom has also been shown to increase teacher professionalism with a coefficient value of 0.301 and a significance of 0.002 0.05. Based on these findings, it can be concluded that the use of Google Classroom can improve the ability to design learning media and teacher professionalism, so it is expected to be a reference in the development of technology-based learning in schools. This research contributes to the development of teacher competencies in the digital era and encourages policies that support the use of technology in learning.